(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
New dangers – including emergent infectious diseases and tragic incidents of civilian mass casualties – pose serious and immediate threats to the population. This implies the need to identify a priori substantial limits within which the (temporary) sus-pension of fundamental human rights can possibly be arranged to protect individual and collective health